2009
DOI: 10.1097/brs.0b013e3181bd09f5
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain Following Vertical Expandable Prosthetic Titanium Ribs Surgery in Children With Thoracic Insufficiency Syndrome

Abstract: A total of 79% of patients with TIS were less than 5 percentile in weight, thus meeting the criteria for "failure to thrive." Our study demonstrates a significant improvement in the nutritional status of these children after VEPTR surgery, which is an important outcome measure in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 6 publications
1
19
0
1
Order By: Relevance
“…Several studies used weight gain as an indirect marker of improved pulmonary function and found that up to 50% of patients with EOS demonstrated a mean 24-to 26-percentagepoint improvement after VEPTR or growing rod treatment. 58,59 Overnight polysomnography in children with EOS demonstrates an increased Apnea-Hypopnea Index 8…”
Section: Pulmonary Outcomes Of Recent Eos Treatmentmentioning
confidence: 99%
“…Several studies used weight gain as an indirect marker of improved pulmonary function and found that up to 50% of patients with EOS demonstrated a mean 24-to 26-percentagepoint improvement after VEPTR or growing rod treatment. 58,59 Overnight polysomnography in children with EOS demonstrates an increased Apnea-Hypopnea Index 8…”
Section: Pulmonary Outcomes Of Recent Eos Treatmentmentioning
confidence: 99%
“…In severe respiratory insufficiency, even oral nutritional intake may represent a challenge because the patient may not tolerate the small breathing pause due to eating [18][19][20]. Our patient was described as having major difficulties in gaining weight all his life and had suffered from a poor appetite for years due to abdominal pain immediately after oral food intake, which worsened his nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…Vitale and co-workers [9] noted a very poor quality of life questionnaire scores for untreated children with thoracic insufficiency syndrome. Skaggs et al [10] found that in 76 patients with TIS, 79 % were under the 5th percentile for weight, and after VEPTR surgery 40 % improved with weight gain. VEPTR appears to make a positive difference for children with thoracic insufficiency syndrome clinically, but the lack of an objective lab test or imaging technique to measure thoracic insufficiency syndrome has made it difficult for orthopedists to fully understand the effect of VEPTR treatment on TIS.…”
Section: Keyword Veptrmentioning
confidence: 99%
“…These volumes were also compared to the retrospective spontaneously breathing pediatric normative CT scan lung volumes reported by Gollogly et al [21], and there was no increase in the age-corrected volumes. The authors also found nearly normal quality of life both before and after VEPTR treatment based on a modified SRS-22 instrument, although a validated Child Health Care Questionnaire study of children by Vitale et al [10] in 2008 showed a marked decrease in quality of life for children with untreated thoracic insufficiency syndrome. The authors' final conclusion was that ''pulmonary function, lung volume, and patient subjective assessments did not increase dramatically after VEPTR placement'', which apparently was their working hypothesis, but the marked heterogeneity of their patient population and their suboptimal age of intervention may have influenced pulmonary outcomes in an unpredictable fashion, and their choice of a quality of life instrument may be unsuited for thoracic insufficiency syndrome.…”
Section: S114mentioning
confidence: 99%